Sexuality, Sociality, and Cosmology in Medieval Literary Texts
XII, 194 p.
Keywords: Exploring the relation between sexuality and cosmology in a variety of literary texts from the tenth to the sixteenth centuries, the essays reveal that medieval authors, whether lay or religious, Christian or Jewish, were grappling with the same sets of questions about sexuality as people are today.